2022
DOI: 10.3390/toxics10010013
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal PM2.5 Exposure in Relation to Maternal and Newborn Telomere Length at Delivery

Abstract: Particulate matter with an aerodynamic diameter of 2.5 μm or less (PM2.5) is a ubiquitous air pollutant that is increasingly threatening the health of adults and children worldwide. One health impact of elevated PM2.5 exposure is alterations in telomere length (TL)—protective caps on chromosome ends that shorten with each cell division. Few analyses involve prenatal PM2.5 exposure, and paired maternal and cord TL measurements. Here, we analyzed the association between average and trimester-specific prenatal PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The available literature on the relationship between telomere length and exposure to air pollutants is primarily from studies measuring the ambient air quality at a population level [24,38]. In our study, we have individual data on the exposure to biomass fuel from each household and LTL measured when the children were 18-23 months.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature on the relationship between telomere length and exposure to air pollutants is primarily from studies measuring the ambient air quality at a population level [24,38]. In our study, we have individual data on the exposure to biomass fuel from each household and LTL measured when the children were 18-23 months.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding environmental exposures, air pollution has been shown to shorten telomere length in several cell types, including leukocytes, placenta, and lung epithelial cells ( Zhao et al, 2018a ; Chang-Chien et al, 2021 ), which directly correlates with accelerated aging ( Pieters et al, 2016 ), and cognitive decline in the elderly ( Colicino et al, 2017 ). Alarmingly, prenatal exposure to air pollution resulted in shorter leukocyte telomere length at birth ( Lee et al, 2020 ; Durham et al, 2022 ). One follow-up study showed these prenatally exposed children had a significant increase in repeated wheeze tests 4 years later.…”
Section: Primary Hallmarks Of Aging: Genomic Instability Telomere Att...mentioning
confidence: 99%